IPO-UNDERPRICING: REPUTASI UNDERWRITER DAN TINGKAT PENGEMBALIAN OPERASI ASET - Ari Purwanti (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
The condition of underpricing at the time of the initial public offering (IPO) on the Indonesian stock exchange which is influenced by the rate of return on assets and the reputation of the underwriters is the purpose of this research. There are 84 companies used as research samples from 159 companies that experienced underpricing conditions during the period 2015 to 2019 on the Indonesia Stock Exchange. By using multiple linear regression in the hypothesis testing method, this study proves that the underwriter's reputation and the rate of return on assets have a negative effect on the underpricing condition. This empirical result shows that companies with higher asset performance and using reputable underwriters are proven to reduce underpricing conditions at the time of the IPO.